The methanol leaf extract of Picralima nitida mitigated cisplatin-induced toxicities in rats through nuclear factor kappa beta, cardiac troponin, mineralocorticoid receptor, and Nrf2 signaling pathways - Adeolu Alex Adedapo; Ademola Afeez Yusuf; Olufunke Olubunmi Falayi; Iyanuoluwa Omolola Ogunmiluyi; Blessing Seun Ogunpolu; Temidayo Olutayo Omobowale; Ademola Adetokunbo Oyagbemi; Olumuyiwa Abiola Adejumobi; Oluwafemi Omoniyi Oguntibeju; Momoh Audu Yakubu; Fred Bayo Yakubu (Shahrekord University of Medical Sciences, 2022)
Introduction: Cisplatin (CP)-induced toxicity involves oxidative stress and Picralima nitida is rich in natural antioxidants hence its methanol leaf extract was used to mitigate the toxic effect of CP.Methods: Forty rats divided into four groups of 10 rats per group were used as follows: group A (normal saline), group B (CP 10 mg/kg), group C [Methanol Leaf Extract of Picralima nitida (MLEPN), 100 mg/kg and CP 10 mg/kg], and group D (MLEPN 200 mg/kg and CP 10 mg/kg). All administrations were done by oral gavage with the volumes of the treatments administered determined by the average weight of the rats in each group except CP, which was given intraperitoneally. Administration of normal saline and MLEPN lasted for seven consecutive days after which a single dose of CP was given on day 8. All animals were sacrificed 72 hours after CP administration. On day 9, blood pressure measurement was taken, and changes in body weight were determined. On day 10, blood samples were taken for serum chemistry, and kidneys, liver, and heart were harvested from the animals for Serum assay, histopathology, and immunohistochemistry, respectively.Results: The extract improved weight changes caused by CP and reversed the toxic changes produced by CP on serum chemistry, oxidative stress, and histopathology. The extract caused a significant decrease in the levels of nuclear factor kappa beta, cardiac troponin, and mineralocorticoid receptors (MCRs). However, it increased the protein expression of Nrf2 compared to the toxicant group.Conclusion: The extract exhibited anti-inflammatory, antioxidant, and anti-renin properties.